IMPLEMENTASI MARKETING SYARIAH BERBASIS INTERNET MARKETING PADA TOKO LANTABUR SIDOARJO - Alifian Bayu (STAI AN-NAJAH INDONESIA MANDIRI, 2020)
Business competition is very tight in the industrial era 4.0, requiring companies to further improve the quality of goods and services, prices, promotions, services to consumers and to understand the needs and wants and consumers. Therefore, in conducting business competition, the company is certainly doing its best. In realizing these things, it is not uncommon for companies to do everything they can to achieve them, resulting in unfair competition. To avoid unfair competition, it is necessary to prepare a marketing concept that is in accordance with sharia. This concept is called the sharia marketing strategy which aims to map the market based on market size, market growth, competitive advantage and competitive situation. At the initial stage, target a potential rational market and continue with positioning in the minds of consumers. The next activity is the sharia marketing strategy which is intended to win market share. In addition, Islamic marketing values ​​also emphasize the brand (brand), which is a good name that becomes the identity of a person or company. Ultimately every business must reflect the level of quality, cost, and delivery of a good product or service to offer. With the various components of marketing based on the principles of Islamic values, the rational market can be more easily brought into the spiritual market area. This research is a type of field research, using two types of data sources, namely primary data and secondary data obtained using interview and documentation methods. After the data is collected, then the data is analyzed using a qualitative descriptive approach. The results of this study state that the marketing carried out by Toko Lantabur is broadly in accordance with the theory of sharia marketing which includes the characteristics of sharia marketing, the principles and marketing practices of the Prophet. And applied in the marketing mix (marketing mix) which consists of four elements, namely, distribution channels (place), product goods or services (product), price (price) and promotion (promotion). The application of Sharia Marketing for Toko Lantabur includes characteristics and principles of Sharia Marketing such as: Theitis Rabbaniyah) prioritizing religious values, Ethical (Akhlaqiyah) maintaining behavior and services, Realistic (Al-Waqi-i'yyah) being professional and flexible, Humanistic (Insaniyyah). Syariah Marketing Strategy which includes segmenting, targeting, positioning. Keywords: Business Competition, Marketing Strategy, Sharia Marketing